146k views
1 vote
-15x²+7x+23=0 i just need the answer of it even it's not correct charr cge na loves​

User Denman
by
5.4k points

1 Answer

2 votes

Use the quadratic formula where -15 = a, 7 = b, 23 = c:
(-b +- √(b^2 - 4ac))/(2a)

Plug in the values:
(-7 +- √(7^2 - 4(-15)(23)))/(2(-15))

And get:
(-7 +- √(49 +1380))/(-30)

Which simplifies to:
(-7 +- √(1429))/(-30) = (-7 + 37.8021163)/-30 OR (-7 - 37.8021163)/-30 = 30.8021163/30 OR -44.8021163/30

Those are approximately 1 and -1.5

User Watt
by
6.4k points